Germline thymidylate synthase deficiency impacts nucleotide metabolism and causes dyskeratosis congenita - Tummala, Hemanth; Walne, Amanda; Buccafusca, Roberto; Alnajar, Jenna; Szabo, Anita; Robinson, Peter; McConkie-Rosell, Allyn; Wilson, Meredith; Crowley, Suzanne; Kinsler, Veronica; Ewins, Anna-Maria; Madapura, Pradeepa M; et al. (American journal of human genetics, 2022)
Dyskeratosis congenita (DC) is an inherited bone-marrow-failure disorder characterized by a triad of mucocutaneous features that include abnormal skin pigmentation, nail dystrophy, and oral leucoplakia. Despite the identification of several genetic variants that cause DC, a significant proportion of probands remain without a molecular diagnosis. In a cohort of eight independent DC-affected families, we have identified a remarkable series of heterozygous germline variants in the gene encoding thymidylate synthase (TYMS). Although the inheritance appeared to be autosomal recessive, one parent in each family had a wild-type TYMS coding sequence. Targeted genomic sequencing identified a specific haplotype and rare variants in the naturally occurring TYMS antisense regulator ENOSF1 (enolase super family 1) inherited from the other parent. Lymphoblastoid cells from affected probands have severe TYMS deficiency, altered cellular deoxyribonucleotide triphosphate pools, and hypersensitivity to the TYMS-specific inhibitor 5-fluorouracil. These defects in the nucleotide metabolism pathway resulted in genotoxic stress, defective transcription, and abnormal telomere maintenance. Gene-rescue studies in cells from affected probands revealed that post-transcriptional epistatic silencing of TYMS is occurring via elevated ENOSF1. These cell and molecular abnormalities generated by the combination of germline digenic variants at the TYMS-ENOSF1 locus represent a unique pathogenetic pathway for DC causation in these affected individuals, whereas the parents who are carriers of either of these variants in a singular fashion remain unaffected.